Availability of hospital‐based cancer services before and after rural hospital closure, 2008‐2017. Issue 2 (21st September 2022) - Zahnd, Whitney E.; Hung, Peiyin; Shi, Sylvia Kewei; Zgodic, Anja; Merrell, Melinda A.; Crouch, Elizabeth L.; Probst, Janice C.; Eberth, Jan M.
Abstract: Introduction: Rural populations have less access to cancer care services and experience higher cancer mortality rates than their urban counterparts, which may be exacerbated by hospital closures. Our objective was to examine the impact of hospital closures on access to cancer‐relevant hospital services across hospital service areas (HSAs). Methods: We used American Hospital Association survey data from 2008 to 2017 to examine the change in access to cancer‐related screening and treatment services across rural HSAs that sustained hospitals over time, experienced any closures, or had all hospitals close. We performed a longitudinal analysis to assess the association between hospital closure occurrence and maintenance or loss of cancer‐related service lines accounting for hospital and HSA‐level characteristics. Maps were also developed to display changes in the availability of services across HSAs. Results: Of the 2, 014 rural HSAs, 3.8% experienced at least 1 hospital closure during the study period, most occurring in the South. Among HSAs that experienced hospital closure, the loss of surgery services lines was most common, while hospital closures did not affect the availability of overall oncology and radiation services. Screening services either were stable (mammography) or increased (endoscopy) in areas with no closures. Discussion: Rural areas persistently experience less access to cancer treatment services, which has been exacerbated by hospital closures. Lack of Medicaid expansion in many Southern states and other policy impacts on hospital financial viability may play a role in this. Future research should explore the impact of closures on cancer treatment receipt and outcomes.